O ENSINO DE ELETRICIDADE NO QUARTO ANO DO ENSINO FUNDAMENTAL - Pereira Junior, Paulo Ricardo Cristofio (2012)
The purpose of this work aims to teach electricity to children in the fourth year of elementary school. To achieve this objective we have developed different activities, gathered in a Didactic Module, prepared in accordance with the methodology of Three Pedagogical Moments , proposed by Angotti and Delizoicov (1991). These activities were divided into four classes, each one with a different activity. These activities have made use household materials such as lamps, batteries, and toys. Just as we used comics with the theme electricity and also a Learning Object of type simulation. The realization of the activities took place in a private school, located in Rosario do Sul / RS. This work was based on the theory of Vygotsky and meaningful learning theory of Ausubel. For authors are able to contribute to the improvement of learning by analyzing previous knowledge of the individual and then make the blend of old and new concepts. This work showed that students were able to develop the proposed activities even taking into account his age (10 years) and make a correlation between the topic covered in the classroom with what they experience in their daily lives.